A method for preparing high-stability perovskite solar cells
By using organic small molecules 4- (4- (9H-Kaazazo-9-yield) ionyl) phenylpylene as a passivation agent by using an organic small molecule in the solar cell), filling ion defects and combined with lead ions, solving perovskite The problems of defects and ultraviolet light damage caused by ore solar batteries during heating and annealing have significantly improved their stability and efficiency.
Patent Information
- Application Number
- CN202411562503.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-05
AI Technical Summary
Perovskite solar cells generate boundary ion vacancies during heating and annealing, resulting in defects and UV light destruction, affecting their stability and efficiency.
The organic small molecule 4-(4-(9H-carbazol-9-yl)styryl)benzonitrile is used as a passivator, and its polar ends are used to fill the ion defects on the surface of the perovskite film and combine with the surface defects Coordinated lead ions reduce the number of defects and simultaneously act as a UV sunscreen to improve stability.
A significant reduction in the number of defects in the perovskite body, improving the stability of ultraviolet light, and improving the efficiency and stability of the battery device.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of perovskite solar cell preparation, and in particular to a method for preparing a high-stability perovskite solar cell. Background Art
[0002] Perovskite solar cells have the advantages of long carrier diffusion length, adjustable band gap, high absorption coefficient and low preparation cost. Their photoelectric conversion efficiency has achieved very rapid development since its birth, and the current highest photoelectric conversion efficiency has exceeded 26%.
[0003] However, during the heating and annealing process of the film prepared by the solvent method, a large number of boundary ion vacancies will be generated at the grain boundaries, resulting in defects at deeper energy levels. Photogenerated carriers are easily captured by these defects, resulting in non-radiative recombination and hindering the conduction of carriers. In addition, ultraviolet light will catalyze and induce irreversible degradation of perovskite, seriously affecting the efficiency and stability of perovskite solar cells. Therefore, developing a passivator molecule that can simultaneously achieve defect filling and ultraviolet filtering can effectively solve the above problems.
[0004] The existing technologies for filling the vacancies of surface ions or inhibiting their generation mainly include: adding excess boundary component ions to the perovskite precursor to compensate for the loss of surface components during the solvent method of preparing thin films, and inhibiting the occurrence of imbalance in the stoichiometric ratio of the perovskite surface. Alternatively, directly adding metal or ammonium halide to the perovskite precursor to form ionic bonds to compensate for vacancies or release lattice stress can also effectively reduce the generation of surface defects.
[0005] However, these strategies mainly focus on suppressing the generation of surface ion defects during the film preparation process. Under the continuous action of ultraviolet radiation, perovskite films are still vulnerable to damage by ultraviolet light. In addition, water molecules can also corrode the skeleton of perovskite, causing its structure to collapse. Summary of the invention
[0006] The present invention aims to solve at least one of the technical problems existing in the related art. To this end, the present invention provides a method for preparing a high-stability perovskite solar cell, which can significantly improve the stability of the perovskite solar cell.
[0007] The present invention provides a method for preparing a high-stability perovskite solar cell, comprising the following steps:
[0008] S100, dissolving zinc acetate dihydrate and magnesium acetate tetrahydrate in a first solvent to obtain a first mixed solution; spin-coating the first mixed solution on a transparent conductive glass substrate with fluorine-doped tin oxide to obtain a spin-coated substrate; annealing the spin-coated substrate to obtain an electron transport layer;
[0009] S200, immersing the electron transport layer in a TiCl4 solution and performing a heating treatment; spin coating the mesoporous slurry on the surface of the electron transport layer after the heating treatment, and performing an annealing treatment to obtain a TiO2 mesoporous layer;
[0010] S300, dissolving CsI and RbI in a second solvent to obtain a second mixed solution; adding the second mixed solution, FAI, MABr and PbI2 into a third solvent to obtain a third mixed solution; dissolving a passivator in the third mixed solution to obtain a precursor solution; wherein the passivator is 4-(4-(9H-carbazole-9-yl)phenylvinyl)benzonitrile;
[0011] S400, spin-coating the precursor solution on the surface of the TiO2 mesoporous layer, adding an anti-solvent, and then annealing to obtain a perovskite solar cell.
[0012] According to a method for preparing a high-stability perovskite solar cell provided by the present invention, the first solvent is at least one of 2-aminoethanol and 2-methoxyethanol.
[0013] According to a method for preparing a high-stability perovskite solar cell provided by the present invention, the mass ratio of the zinc acetate dihydrate to the magnesium acetate tetrahydrate is (3-5):1.
[0014] According to a method for preparing a high-stability perovskite solar cell provided by the present invention, in the step S100, the temperature of the annealing treatment is 300°C to 500°C.
[0015] According to a method for preparing a high-stability perovskite solar cell provided by the present invention, in the step S200, the concentration of the TiCl4 solution is 20 mmol / L, the heating temperature of the heating treatment is 50°C to 100°C, and the temperature of the annealing treatment is 300°C to 500°C;
[0016] The mesoporous slurry is prepared by uniformly dispersing Dyesol DSL18NR-T and isopropanol in a mass ratio of 1:10.
[0017] According to a method for preparing a high-stability perovskite solar cell provided by the present invention, in the step S300, the mass ratio of the CsI to the RbI is 1.2:1; the masses of the FAI, the MABr and the PbI2 are 3.6 times, 0.35 times and 9.4 times the mass of the RbI, respectively;
[0018] The second solvent is a polar solvent, the third solvent is a mixed solvent of DMF solvent and DMSO solvent, and the volume ratio of the DMF solvent to the DMSO solvent is 4:1.
[0019] According to a method for preparing a high-stability perovskite solar cell provided by the present invention, in the step S400, the anti-solvent is a non-polar solvent, and the temperature of the annealing treatment is 90° C. to 150° C.
[0020] According to a method for preparing a high-stability perovskite solar cell provided by the present invention, in the step S300, the passivator is 4-(4-(9H-carbazole-9-yl)phenylvinyl)benzonitrile; the preparation method of the passivator comprises the following steps:
[0021] 4-carbazole benzaldehyde, diethyl (4-cyanobenzyl)phosphonate and dry tetrahydrofuran are mixed to obtain a mixture;
[0022] In the first environment, a tetrahydrofuran solution of potassium tert-butoxide is added dropwise to the mixture, and after the reaction starts, the mixture is adjusted to the second environment and the reaction is continued for 30 minutes, after which water is added to quench the reaction and precipitate a crude product;
[0023] The crude product is washed with ethanol, and then the crude product is recrystallized with ethyl acetate to obtain a passivating agent;
[0024] The first environment is an environment below 0° C. under the protection of argon gas, and the second environment is an environment at room temperature under the protection of argon gas.
[0025] The above one or more technical solutions in the embodiments of the present invention have at least one of the following technical effects:
[0026] The method for preparing a high-stability perovskite solar cell provided by the present invention comprises the following steps:
[0027] S100, dissolving zinc acetate dihydrate and magnesium acetate tetrahydrate in a first solvent to obtain a first mixed solution; spin-coating the first mixed solution on a transparent conductive glass substrate with fluorine-doped tin oxide to obtain a spin-coated substrate; annealing the spin-coated substrate to obtain an electron transport layer;
[0028] S200, immersing the electron transport layer in a TiCl4 solution and performing a heating treatment; spin coating the mesoporous slurry on the surface of the electron transport layer after the heating treatment, and performing an annealing treatment to obtain a TiO2 mesoporous layer;
[0029] S300, dissolving CsI and RbI in a second solvent to obtain a second mixed solution; adding the second mixed solution, FAI, MABr and PbI2 into a third solvent to obtain a third mixed solution; dissolving a passivating agent in the third mixed solution to obtain a precursor solution;
[0030] S400, spin coating the precursor solution on the surface of the TiO2 mesoporous layer, and adding an anti-solvent, followed by annealing to obtain a perovskite solar cell; by using the organic small molecule 4-(4-(9H-carbazole-9-yl)phenylvinyl)benzonitrile as a passivator, the polar end of the organic small molecule 4-(4-(9H-carbazole-9-yl)phenylvinyl)benzonitrile is used to fill the ion defects on the surface of the perovskite film, and at the same time effectively binds to the lead ions that lack coordination on the surface, significantly reducing the number of defects in the perovskite bulk phase; and the passivator has a high absorption coefficient for ultraviolet light, and can be used as a UV sunscreen for the perovskite film to improve the stability of the perovskite when exposed to light; at the same time, the passivator itself has good hydrophobicity, and is anchored on the surface of the perovskite lattice, effectively preventing water molecules from invading and destroying the perovskite crystal structure, and the modified battery device shows a significant improvement in efficiency and stability.
[0031] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. The following embodiments are used to illustrate the present invention, but cannot be used to limit the scope of the present invention.
[0033] In the description of the embodiments of the present invention, it should be noted that the terms “first”, “second” and “third” are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.
[0034] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the embodiment of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0035] The following describes a method for preparing a high-stability perovskite solar cell according to the present invention, comprising the following steps:
[0036] S100, dissolving zinc acetate dihydrate and magnesium acetate tetrahydrate in a first solvent to obtain a first mixed solution; spin-coating the first mixed solution on a transparent conductive glass substrate with fluorine-doped tin oxide to obtain a spin-coated substrate; annealing the spin-coated substrate to obtain an electron transport layer.
[0037] In this embodiment, the first solvent is at least one of 2-aminoethanol and 2-methoxyethanol. The mass ratio of the zinc acetate dihydrate to the magnesium acetate tetrahydrate is (3-5):1, preferably 3.4:1. The annealing temperature is 300°C-500°C, preferably 500°C.
[0038] S200, immersing the electron transport layer in a TiCl4 solution and performing a heat treatment; spin coating the mesoporous slurry on the surface of the electron transport layer after the heat treatment, and performing an annealing treatment to obtain a TiO2 mesoporous layer.
[0039] Wherein, the concentration of TiCl4 solution is 20mmol / L, the heating temperature of the heating treatment is 50℃~100℃, preferably 70℃; the temperature of the annealing treatment is 300℃~500℃, preferably 500℃;
[0040] The mesoporous slurry is prepared by uniformly dispersing Dyesol DSL18NR-T and isopropanol in a mass ratio of 1:10.
[0041] S300, dissolving CsI and RbI in a second solvent to obtain a second mixed solution; adding the second mixed solution, FAI, MABr and PbI2 into a third solvent to obtain a third mixed solution; dissolving a passivating agent in the third mixed solution to obtain a precursor solution;
[0042] The passivator is 4-(4-(9H-carbazole-9-yl)phenylvinyl)benzonitrile, which uses its own polar end to fill the ion defects on the surface of the perovskite film, and effectively combines the lead ions that lack coordination on the surface, significantly reducing the number of defects in the perovskite bulk phase; and the passivator has a high absorption coefficient for ultraviolet light, and can be well used as an ultraviolet sunscreen for perovskite films to improve the stability of perovskite exposed to light; at the same time, the passivator itself has good hydrophobicity, and it is anchored on the surface of the perovskite lattice, effectively preventing water molecules from invading and destroying the perovskite crystal structure, and the modified battery device shows a significant improvement in efficiency and stability.
[0043] The mass ratio of the CsI to the RbI is 1.2:1; the masses of the FAI, the MABr and the PbI2 are 3.6 times, 0.35 times and 9.4 times the mass of the RbI, respectively;
[0044] The second solvent is a polar solvent, and in this embodiment, it is DMSO solvent. The third solvent is a mixed solvent of DMF solvent and DMSO solvent, and the volume ratio of the DMF solvent to the DMSO solvent is 4:1.
[0045] Furthermore, the passivator is 4-(4-(9H-carbazole-9-yl)phenylvinyl)benzonitrile; and the preparation method of the passivator comprises the following steps:
[0046] 4-carbazole benzaldehyde, diethyl (4-cyanobenzyl)phosphonate and dry tetrahydrofuran are mixed to obtain a mixture;
[0047] In the first environment, a tetrahydrofuran solution of potassium tert-butoxide is added dropwise to the mixture, and after the reaction starts, the mixture is adjusted to the second environment and the reaction is continued for 30 minutes, after which water is added to quench the reaction and precipitate a crude product;
[0048] The crude product was washed with ethanol, and then recrystallized with ethyl acetate to obtain a passivating agent.
[0049] S400, spin-coating the precursor solution on the surface of the TiO2 mesoporous layer, adding an anti-solvent, and then annealing to obtain a perovskite solar cell.
[0050] The anti-solvent is a non-polar solvent, which is chlorobenzene in this embodiment. The annealing temperature is 90°C to 150°C, preferably 120°C.
[0051] In order to test the efficiency and stability of perovskite solar cells, the Spiro-OMeTAD solution was spin-coated on the surface of the perovskite layer of the perovskite solar cell to test the efficiency of the perovskite solar cell. The P3HT solution was spin-coated on the surface of the perovskite layer of the perovskite solar cell to test the stability of the perovskite solar cell.
[0052] The Spiro-OMeTAD solution is a mixed solution consisting of a chlorobenzene solution of Spiro-OMeTAD, a tert-butylpyridine solution and an acetonitrile solution of Li-TFSI. The P3HT solution is prepared by dissolving P3HT in a chlorobenzene solution.
[0053] The performance characterization test benchmark of the perovskite solar cell prepared based on a method for preparing a high-stability perovskite solar cell in the present invention is:
[0054] A solar simulator (aperture 40 × 40 cm) equipped with a Keithley 2400 source meter and a 300 W collimated xenon lamp was used. 2) to test the volt-ampere characteristic curve of the solar cell device. Before the test, the light intensity needs to be calibrated to 100mW•cm under simulated AM1.5G light using a standard silicon solar cell. -2 .
[0055] The battery device efficiency test uses the FTO / Modified-ZnO / Meso-TiO2 / Perovskite / Spiro-OMeTAD / Au battery structure. The stability test uses the FTO / Modified-ZnO / Meso-TiO2 / Perovskite / P3HT / Au battery structure.
[0056] Under argon protection, 4-carbazole benzaldehyde (258 mg, 1 mmol) and (4-cyanobenzyl) diethyl phosphonate (253 mg, 1 mmol) were added to a sealed and dry three-necked flask, and then 10 mL of dry tetrahydrofuran was added, and the mixture was kept stirring at 0 °C. After that, a tetrahydrofuran solution of potassium tert-butoxide (2 mmol, 20 mL) was slowly added dropwise to the reaction system. After the addition was completed, the mixture was slowly heated to room temperature (the specific operation was to remove the 0 °C ice water bath) and continued to stir for 30 min. Then, 20 mL of deionized water was added to the reaction system to quench the reaction. The precipitated solid was washed with anhydrous ethanol, and then the crude product was recrystallized with ethyl acetate to complete the preparation of the passivating agent. The environment below 0 °C under argon protection was the first environment, and the room temperature environment under argon protection was the second environment.
[0057] The final yield of the passivating agent was 70%. MALDI-TOF (m / z) mass spectrometer analysis: calculated value (C 27 H 18 N2): 370.15; Test value: 370.01. The absorption spectrum of the compound shows that it has a high absorption coefficient in the ultraviolet region, which can reach 1.4×10 4 L / mol•cm
[0058] Example 1
[0059] A method for preparing a high-stability perovskite solar cell comprises the following steps:
[0060] S100, dissolving zinc acetate dihydrate and magnesium acetate tetrahydrate in a mass ratio of 3:1 in 2-aminoethanol to obtain a first mixed solution; spin-coating the first mixed solution on a transparent conductive glass substrate with fluorine-doped tin oxide to obtain a spin-coated substrate; annealing the spin-coated substrate at a temperature of 300° C. to obtain an electron transport layer.
[0061] S200, immersing the electron transport layer in a TiCl4 solution with a concentration of 20mmol / L and heating it at a temperature of 50°C; spin-coating the mesoporous slurry on the surface of the heated electron transport layer and annealing it at a temperature of 300°C to obtain a TiO2 mesoporous layer. The mesoporous slurry is prepared by uniformly dispersing Dyesol DSL18NR-T and isopropanol at a mass ratio of 1:10.
[0062] S300, dissolving CsI and RbI in a mass ratio of 1.2:1 in DMSO solvent to obtain a second mixed solution; adding the second mixed solution, FAI, MABr and PbI2 whose masses are 3.6 times, 0.35 times and 9.4 times the mass of the RbI respectively, to a mixed solvent of DMF solvent and DMSO solvent to obtain a third mixed solution; dissolving 0.1% of a passivating agent relative to the molar number of PbI2 in the third mixed solution to prepare a precursor solution; wherein the volume ratio of the DMF solvent to the DMSO solvent is 4:1.
[0063] S400, spin-coating the precursor solution on the surface of the TiO2 mesoporous layer, and dropping chlorobenzene, followed by annealing treatment at a temperature of 90° C., to obtain a perovskite solar cell.
[0064] Example 2
[0065] A method for preparing a high-stability perovskite solar cell comprises the following steps:
[0066] S100, dissolving zinc acetate dihydrate and magnesium acetate tetrahydrate in a mass ratio of 3.4:1 in 2-methoxyethanol to obtain a first mixed solution; spin-coating the first mixed solution on a transparent conductive glass substrate with fluorine-doped tin oxide to obtain a spin-coated substrate; annealing the spin-coated substrate at a temperature of 500° C. to obtain an electron transport layer.
[0067] S200, immersing the electron transport layer in a TiCl4 solution with a concentration of 20 mmol / L, and heating it at a temperature of 70°C; spin-coating the mesoporous slurry on the surface of the electron transport layer after the heating treatment, and annealing it at a temperature of 500°C to obtain a TiO2 mesoporous layer.
[0068] The mesoporous slurry is prepared by uniformly dispersing Dyesol DSL18NR-T and isopropanol in a mass ratio of 1:10.
[0069] S300, dissolving CsI and RbI in a mass ratio of 1.2:1 in DMSO solvent to obtain a second mixed solution; adding the second mixed solution, FAI, MABr and PbI2 whose masses are 3.6 times, 0.35 times and 9.4 times the mass of the RbI respectively to a third solvent to obtain a third mixed solution; dissolving 0.2% of a passivator relative to the molar number of PbI2 in the third mixed solution to obtain a precursor solution; wherein the third solvent is a mixed solvent of DMF solvent and DMSO solvent, and the volume ratio of the DMF solvent to the DMSO solvent is 4:1.
[0070] S400, spin-coating the precursor solution on the surface of the TiO2 mesoporous layer, and dropping chlorobenzene, followed by annealing treatment at a temperature of 120° C., to obtain a perovskite solar cell.
[0071] Example 3
[0072] A method for preparing a high-stability perovskite solar cell comprises the following steps:
[0073] S100, dissolving zinc acetate dihydrate and magnesium acetate tetrahydrate in a ratio of 5:1 in a first solvent to obtain a first mixed solution; the first solvent is a mixed solvent of 2-aminoethanol and 2-methoxyethanol. Spin-coating the first mixed solution on a transparent conductive glass substrate with fluorine-doped tin oxide to obtain a spin-coated substrate; annealing the spin-coated substrate at a temperature of 400° C. to obtain an electron transport layer.
[0074] S200, immersing the electron transport layer in a TiCl4 solution with a concentration of 20 mmol / L, and heating it at a temperature of 100°C; spin-coating the mesoporous slurry on the surface of the electron transport layer after the heating treatment, and annealing it at a temperature of 400°C to obtain a TiO2 mesoporous layer. The mesoporous slurry is prepared by uniformly dispersing Dyesol DSL18NR-T and isopropanol at a mass ratio of 1:10.
[0075] S300, dissolving CsI and RbI in a mass ratio of 1.2:1 in DMSO solvent to obtain a second mixed solution; adding the second mixed solution, FAI, MABr and PbI2 whose masses are 3.6 times, 0.35 times and 9.4 times the mass of the RbI respectively to a third solvent to obtain a third mixed solution; dissolving 0.3% of a passivator relative to the molar number of PbI2 in the third mixed solution to obtain a precursor solution; wherein the third solvent is a mixed solvent of DMF solvent and DMSO solvent, and the volume ratio of the DMF solvent to the DMSO solvent is 4:1.
[0076] S400, spin-coating the precursor solution on the surface of the TiO2 mesoporous layer, and dropping chlorobenzene, followed by annealing treatment at a temperature of 150° C., to obtain a perovskite solar cell.
[0077] Comparative Example
[0078] The transparent conductive glass substrate with fluorine-doped tin oxide (FTO) was immersed in acetone, deionized water and anhydrous ethanol respectively and cleaned in an ultrasonic cleaner for 15 minutes. It was then sent to an ultraviolet light cleaner for 15 minutes to obtain a clean substrate for use.
[0079] Preparation of electron transport layer: Dissolve zinc acetate dihydrate (220 mg) and magnesium acetate tetrahydrate (64 mg) in a mixed solvent of 2-aminoethanol (80 μL) and 2-methoxyethanol (3.3 mL). Spin-coat the prepared precursor solution on the FTO substrate (rotation speed 3300 rpm, time 30 s), anneal the spin-coated glass substrate at 500 ° C for 30 min, and then cool to room temperature.
[0080] Preparation of TiO2 mesoporous layer: The prepared substrate was immersed in a TiCl4 solution (20 mM) and heated at 70 °C for 12 min. Then, the prepared mesoporous slurry (Dyesol DSL18NR-T and isopropanol were evenly dispersed in a mass ratio of 1:10) was spin-coated on the electron transport layer substrate at a speed of 5000 rpm for 40 s. Then, the substrate was annealed at 500 °C for 30 min and then cooled to room temperature.
[0081] Preparation of perovskite layer: CsI (77.94 mg) and RbI (63.7 mg) were dissolved in 200 μL of DMSO, and FAI (217 mg), MABr (29 mg), PbI2 (778.7 mg) and the above-prepared CsI / DMSO (62 μL) and RbI / DMSO (61 μL) were dissolved in a mixed solvent of DMF (970 μL) and DMSO (240 μL). The above-prepared perovskite precursor solution was first rotated at a speed of 1000 rpm for 15 seconds, and then rotated at a speed of 4000 rpm for 30 seconds to complete the spin coating of the perovskite precursor solution on the substrate. In the last 5 seconds of the spin coating process, 400 μL of chlorobenzene (as anti-solvent) was quickly added, and then placed on a hot plate for annealing at 150°C for 30 minutes to form a black film.
[0082] Preparation of hole transport layer: Spiro-OMeTAD: Dissolve Spiro-OMeTAD (100 mg) in 1 mL of chlorobenzene and add 24.5 μL of Li-TFSI / acetonitrile (520 mg / mL) and 40.3 μL of tBP. Spin coat the prepared solution on the surface of the perovskite film at 4500 rpm for 30 s. When testing stability, P3HT will be used as the hole transport layer. Dissolve 15 mg of P3HT in 1 mL of chlorobenzene and spin coat the prepared solution on the surface of the perovskite film at 4500 rpm for 25 s.
[0083] Deposition of metal electrodes: Use vacuum evaporation equipment to evaporate Au or Ag onto the surface of the hole transport layer under high vacuum to deposit a metal electrode with a thickness of 50 nm to obtain a perovskite solar cell.
[0084] Demonstration test of enhanced photoelectric capability
[0085] In AM1.5G 100mW•cm -2 Example 1, Example 2, Example 3 and the comparative example (active area of 0.04 cm 2 ), the battery efficiencies corresponding to Example 1, Example 2, and Example 3 are significantly improved relative to the comparative example, wherein the conversion efficiency of Example 1 is the highest at 21.48%, the conversion efficiency of Example 2 is the best, up to 21.89%, the conversion efficiency of Example 3 is the highest at 21.68%, and the conversion efficiency of the comparative example is the highest at 21.01%. It can be seen that the conversion efficiencies of Example 1, Example 2, and Example 3 are significantly higher than those of the comparative example.
[0086] Enhanced performance testing of water stability
[0087] Example 1, Example 2, Example 3 and the comparative example were placed in an environment with room temperature and 65% humidity. After 3200 hours, Example 2 still maintained an initial efficiency of more than 90%, and the initial efficiency of the comparative example was significantly worse than that of Example 1, Example 2 and Example 3, indicating that the water stability of the perovskite solar cell prepared in the embodiment of the present invention is significantly improved. The test results are shown in Table 1.
[0088] Table 1 Water stability test results
[0089]
[0090] Enhanced photostability testing
[0091] Example 1, Example 2, Example 3 and the comparative example were placed in a nitrogen environment and continuously irradiated with ultraviolet light for 700 hours. Example 1, Example 2, Example 3 were still able to maintain good initial efficiency, while the initial efficiency of the comparative example was severely attenuated. The test results are shown in Table 2.
[0092] Table 2 UV stability test
[0093]
[0094] Furthermore, the light stability of Example 1, Example 2, Example 3 and the comparative example was tested under the above conditions. After 1000 hours of simulated sunlight irradiation, Example 1, Example 2 and Example 3 still maintained an initial efficiency of more than 80%, while the initial efficiency of the comparative example was only 43.4%, confirming the improvement of the light stability of the perovskite solar cell used in the embodiments of the present invention. The test results are shown in Table 3.
[0095] Table 3 Simulated sunlight stability test
[0096]
[0097] The above one or more technical solutions in the embodiments of the present invention have at least one of the following technical effects:
[0098] The method for preparing a high-stability perovskite solar cell provided by the present invention comprises the following steps:
[0099] S100, dissolving zinc acetate dihydrate and magnesium acetate tetrahydrate in a first solvent to obtain a first mixed solution; spin-coating the first mixed solution on a transparent conductive glass substrate with fluorine-doped tin oxide to obtain a spin-coated substrate; annealing the spin-coated substrate to obtain an electron transport layer;
[0100] S200, immersing the electron transport layer in a TiCl4 solution and performing a heating treatment; spin coating the mesoporous slurry on the surface of the electron transport layer after the heating treatment, and performing an annealing treatment to obtain a TiO2 mesoporous layer;
[0101] S300, dissolving CsI and RbI in a second solvent to obtain a second mixed solution; adding the second mixed solution, FAI, MABr and PbI2 into a third solvent to obtain a third mixed solution; dissolving a passivating agent in the third mixed solution to obtain a precursor solution;
[0102] S400, spin coating the precursor solution on the surface of the TiO2 mesoporous layer, and adding an anti-solvent, followed by annealing to obtain a perovskite solar cell; by using the organic small molecule 4-(4-(9H-carbazole-9-yl)phenylvinyl)benzonitrile as a passivator, the polar end of the organic small molecule 4-(4-(9H-carbazole-9-yl)phenylvinyl)benzonitrile is used to fill the ion defects on the surface of the perovskite film, and at the same time effectively binds to the lead ions that lack coordination on the surface, significantly reducing the number of defects in the perovskite bulk phase; and the passivator has a high absorption coefficient for ultraviolet light, and can be used as a UV sunscreen for the perovskite film to improve the stability of the perovskite when exposed to light; at the same time, the passivator itself has good hydrophobicity, and is anchored on the surface of the perovskite lattice, effectively preventing water molecules from invading and destroying the perovskite crystal structure, and the modified battery device shows a significant improvement in efficiency and stability.
[0103] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a high-stability perovskite solar cell, characterized in that: The steps include: S100, dissolving zinc acetate dihydrate and magnesium acetate tetrahydrate in a first solvent to obtain a first mixed solution; spin-coating the first mixed solution on a transparent conductive glass substrate with fluorine-doped tin oxide to obtain a spin-coated substrate; Annealing the spin-coated substrate to obtain an electron transport layer; S200, immersing the electron transport layer in a TiCl4 solution and performing a heating treatment; spin coating the mesoporous slurry on the surface of the electron transport layer after the heating treatment, and performing an annealing treatment to obtain a TiO2 mesoporous layer; S300, dissolving CsI and RbI in a second solvent to obtain a second mixed solution; The second mixed solution, FAI, MABr and PbI2 are added to a third solvent to obtain a third mixed solution; a passivator is dissolved in the third mixed solution to obtain a precursor solution; wherein the passivator is 4-(4-(9H-carbazole-9-yl)phenylvinyl)benzonitrile; S400, spin-coating the precursor solution on the surface of the TiO2 mesoporous layer, adding an anti-solvent, and then annealing to obtain a perovskite solar cell.
2. The method for preparing a high-stability perovskite solar cell according to claim 1, characterized in that: The first solvent is at least one of 2-aminoethanol and 2-methoxyethanol.
3. The method for preparing a high-stability perovskite solar cell according to claim 1, characterized in that: The mass ratio of the zinc acetate dihydrate to the magnesium acetate tetrahydrate is (3-5):
1.
4. The method for preparing a high-stability perovskite solar cell according to claim 1, characterized in that: In the step S100, the temperature of the annealing treatment is 300°C to 500°C.
5. The method for preparing a high-stability perovskite solar cell according to claim 1, characterized in that: In the step S200, the concentration of the TiCl4 solution is 20 mmol / L, the heating temperature of the heating treatment is 50°C to 100°C, and the temperature of the annealing treatment is 300°C to 500°C; The mesoporous slurry is prepared by uniformly dispersing Dyesol DSL18NR-T and isopropanol in a mass ratio of 1:
10.
6. The method for preparing a high-stability perovskite solar cell according to claim 1, characterized in that: In the step S300, the mass ratio of the CsI to the RbI is 1.2:1; the masses of the FAI, the MABr and the PbI2 are 3.6 times, 0.35 times and 9.4 times the mass of the RbI, respectively; The second solvent is a polar solvent, the third solvent is a mixed solvent of DMF solvent and DMSO solvent, and the volume ratio of the DMF solvent to the DMSO solvent is 4:
1.
7. The method for preparing a high-stability perovskite solar cell according to claim 1, characterized in that: In the step S400, the anti-solvent is a non-polar solvent, and the temperature of the annealing treatment is 90°C to 150°C.
8. The method for preparing a high-stability perovskite solar cell according to claim 1, characterized in that: In the step S300, the method for preparing the passivating agent comprises the following steps: 4-carbazole benzaldehyde, diethyl (4-cyanobenzyl)phosphonate and dry tetrahydrofuran are mixed to obtain a mixture; In the first environment, a tetrahydrofuran solution of potassium tert-butoxide is added dropwise to the mixture, and after the reaction starts, the mixture is adjusted to the second environment and the reaction is continued for 30 minutes, after which water is added to quench the reaction and precipitate a crude product; The crude product is washed with ethanol, and then the crude product is recrystallized with ethyl acetate to obtain a passivating agent; The first environment is an environment below 0° C. under the protection of argon gas, and the second environment is an environment at room temperature under the protection of argon gas.
Citation Information
Patent Citations
Phenanthroimidazole luminescent material containing styryl as well as preparation method and application thereof
CN113527211A
High-stability environment-friendly perovskite solar cell
CN115666145A